Helping learners become successful users of english. - Minami, Hiroe (Cinzontle, 2018)
The new course programme of the BA in Modern Languages of the Universidad Juárez Autónoma de Tabasco has been in effect for almost five years. The first generation of this programme is now in the ninth academic period